The Transformative Role of Tuan Guru as a Social Figure and Grand Master of Islam at the Islamic Boarding School - Johansyah Johansyah; Ilmiawan Mubin; Dian Eka Mayasari; Muhammad Hafeez (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2026)
Tuan Guru holds an important position in Lombok society as a spiritual and social leader. It is necessary to understand the balance between two roles that often cause tension: the religious-spiritual role as a religious teacher and the socio-political role as a community leader. Amidst dynamic social changes, Tuan Guru is required to maintain moral integrity while also being an agent of Islamic-based educational and social reform. This study aims to explain the balance between the spiritual-religious and socio-political roles of Tuan Guru. In this context, Tuan Guru is required to maintain moral integrity and religious knowledge while demonstrating adaptive social leadership. This will enable the re-emergence of Islamic leadership, such as that of the Prophet Muhammad which harmonizes religion and statehood. The approach used in this study is qualitative-descriptive. Data collection was carried out through observation at the Nurul Hakim Islamic Boarding School in Kediri, West Lombok, by interviewing various figures, namely the village head, community leaders, village elders, and teachers. This study employs Max Weber’s interactive analysis model, which encompasses data collection, reduction, presentation and drawing of conclusions, enriched by the theory of charismatic authority and the concept of transformational leadership developed by James MacGregor Burns and Bernard M. Bass. This framework is used to interpret Tuan Guru’s charisma as a source of moral legitimacy and to analyze the shift in his role from a religious authority to an actor in social, political, and educational reform. The findings indicate that Tuan Guru’s leadership has transformed from normative religious authority into multidimensional community leadership through strengthened moral legitimacy, social trust, and adaptive capacity in the face of social change. Consequently, Tuan Guru functions as a spiritual guide, moral exemplar, educational reformer, and socio-political mediator. This research makes a theoretical contribution to the study of religious leadership and, in practical terms, provides insights into value-based adaptive leadership for addressing contemporary social challenges.